Konstruksi Perempuan dalam Keluarga Perspektif Kitab al-Tafsīr al-Wasīṭ li al-Qur’ān al-Karīm - Ali Hendri (Institut Ilmu Keislaman Annuqayah, 2019)
Problems as for the roles and positions of women in the family are essential to study. This is because a holistic understanding regarding women will not produce a biased perspective. A biased perspective towards women can be a stepping stone to family problems. In light of that, the research aims to discuss women in the family from the perspective of Muhammad Sayyid Tāntāwī in the book of al-Tafsīr al-Wasīt Li al-Qur' ān al-Karīm by using a descriptive-analytic method, social history, and gender theory. According to the book, the position of women in the household is men's assistance, and the leadership of men towards women is absolute. However, the leadership should be based on asas maslaha (public interest). So too with polygamy and nusyuz, Muhammad Sayyid Tantawi tried to be moderate. Although he allowed polygamy, there should be requirements to be fulfilled and boundaries not to be violated. As for the spiritual side, according to Muhammad Sayyid Tantawi, men and women are equal, and nothing is prioritized.